Webinar career talk: finding passion and resilience - Rizky Yudaruddin; Karina Kausalya Laman; Kharisma Ambarsari; Putri Zhafira Chairunnisa; Silvitri Diah Yulianti (ABDIMU, 2022)
Passion is defined as an affective structure, an optimistic orientation toward work that both produces and gives meaning to a variety of emotional dispositions, whereas The Oxford English Dictionary defines the contemporary use of passion as "an aim or goal pursued with zeal," implying that passion is the active pursuit of something, whether it be real or imagined. In this case, however, the pursuit is typically motivated not by the object itself, but by the promise the object holds. When someone is asked to be passionate about something or their work, the underlying meaning is that finding passion in one's work can lead to certain desirable outcomes, such as competence, success, and self-fulfillment. Whereas resilience is one of the most significant factors that can influence an individual's pursuit of life's passion, resilience can be defined as an ongoing developmental process that demonstrates positive adjustment to adversity. Resilience is also defined as the capacity of a child to effectively deal with stress and pressure, to face daily challenges, to recover from disappointment, mistakes, trauma, and adversity, to set clear and realistic goals, to solve problems, to interact with others comfortably, and to treat oneself and others with respect and dignity. One of the many obstacles a person faces, particularly at the beginning of a higher education endeavor, is the difficulty of locating one's true passion and remaining resilient. Thus, the purpose of this webinar was to share the experiences of four speakers with diverse and impressive backgrounds on how to find passion and resiliency in order to assist the soon to be college students participants.